2015
DOI: 10.1177/1357633x15575830
|View full text |Cite
|
Sign up to set email alerts
|

TulaSalud: An m-health system for maternal and infant mortality reduction in Guatemala

Abstract: SummaryThe Guatemalan NGO (Non-Governmental Organization) TulaSalud has implemented an m-health project in the Department of Alta Verapaz. This Department has 1.2 million inhabitants (78% living in rural areas and 89% from indigenous communities) and in 2012, had a maternal mortality rate of 273 for every 100,000 live births. This m-health initiative is based on the provision of a cell phone to community facilitators (CFs). The CFs are volunteers in rural communities who perform health prevention, promotion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
(16 reference statements)
2
14
0
1
Order By: Relevance
“…For example, in a study conducted in rural Pakistan by Jokhio et al [30], training TBAs to recognize maternal and perinatal complications, alongside efforts made to better integrate them into the formal health system, resulted in increased referral rates to facility-care for emergency obstetrical care. Similarly, a recent study in rural Guatemala connecting community health workers – with higher levels of clinical training and literacy than the TBAs in our study – to medical specialists via cell-phones [31], showed a promising trend toward reductions in maternal mortality.…”
Section: Discussionsupporting
confidence: 67%
“…For example, in a study conducted in rural Pakistan by Jokhio et al [30], training TBAs to recognize maternal and perinatal complications, alongside efforts made to better integrate them into the formal health system, resulted in increased referral rates to facility-care for emergency obstetrical care. Similarly, a recent study in rural Guatemala connecting community health workers – with higher levels of clinical training and literacy than the TBAs in our study – to medical specialists via cell-phones [31], showed a promising trend toward reductions in maternal mortality.…”
Section: Discussionsupporting
confidence: 67%
“…8,9 Despite the advance of e-health technologies through electronic devices, there are relatively few studies that have evaluated the management of high risk pregnant women. 5,6 There may be an increased demand for bidirectional e-health selfcare telemedicine using a smartphone app in high risk pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, through literature reviews, there is limited information regarding the utility of ICTbased maternity data collection and a comprehensive home-based model of care for high risk pregnant women who want to identify obstetric problems earlier and increasing demand for their need and care, implemented through an e-healthcare software. 5,6 We have developed a new model for maternity e-healthcare devices using a tablet-based application that provides a bidirectional communication through e-mails and mobile text messages between pregnant women and trained coordinators/ obstetricians and offers medical advice. The objectives of this study were 1) to determine the usability, feasibility, preliminary efficacy and safety of a tablet-based real-time bidirectional telecommunication of self-reported maternal condition such as body weight, blood pressure and daily symptom questionnaire for 30 days in normal and high risk pregnant women, and 2) to evaluate the effect of a bidirectional and multi-group telemedicine system on satisfaction in these pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that 168 of 273 patients who received the intervention via text messaging responded significantly better when compared to 132 of 265 patients who received face to face care. In Guatemala, Martínez-Fernández et al [27] studied the development of an online health system via text messaging and mobile phones in indigenous rural areas, observing a statistically significant reduction of maternal and infant mortality amongst 6783 pregnant women.…”
Section: Mobile Phones and Social Workmentioning
confidence: 99%